Pancreatic Laceration in a Pediatric Patient: An Unexpected Diagnosis. (2nd November 2017) - Hong, Michelle J.; Porter, Lauren M.; Esernio-Jenssen, Debra D.; Miller, Andrew C.; Greenberg, Marna Rayl
Abstract : Pediatric pancreatic injuries are rare. We present an atypical case that occurred in a 4-year-old male. The child presented with a twenty-four-hour history of vomiting that had progressed to right lower quadrant abdominal pain on examination in the emergency department. The initial differential was gastroenteritis versus appendicitis. An abnormality on the ultrasonography and an elevated lipase level eventually led to an MRI showing a complete transection through the posterior margin of the pancreas. The patient was admitted to pediatric surgery and underwent a successful distal pancreatectomy with preservation of the spleen. On further inquiry specific to trauma, the child disclosed that his older brother had punched him in his abdomen the night before. The child's parents were separated due to intimate partner violence, and this older sibling recently had been very stressed. The sibling was referred for mental health evaluation and counseling, and the case reported to the county children and youth investigative services system. A low threshold for considering trauma and child abuse in the pediatric population is recommended when significant intra-abdominal injury is diagnosed.